Pengantar Tentang Konsep Dasar Siaran Radio ,Televisi Multimedia (Internet) Bermuatan Dakwah - Erwan Efendi; Forsaktinahot Hasugian; Ajulan Siregar; Ahmad Fauzan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Da'wah for Muslims is an obligation and is the responsibility of every Muslim. In the current era of globalization, preachers must be able to keep up with technological sophistication in conveying da'wah, so that the general public can receive every da'wah message properly. Nowadays, the media is one of the easiest tools to convey da'wah. Multimedia da'wah is a da'wah innovation for preachers in Indonesia, preachers can easily deliver da'wah. In this day and age, preachers only need to preach in one place and spread it through the media, be it television, radio or even the one that is most often used today, namely social media (multimedia). da'wah through the media will provide very effective results because many people understand the progress of this sophisticated technology so that the general public can easily see the preachers' various da'wah through television media, radio media and more importantly social media. preachers should use media that are widely spread in the community, such as combining da'wah media through pulpits, audio, radio, television, print media, the internet and even what we see more often, namely social media.